(untitled) (Journal of Dhaka Medical College, 2023)
Background: Pemphigus vulgaris is an autoimmune, potentially fatal vesiculobullous disease of skin and mucous membranes. The clinical profile and epidemiologic characteristics varies in patients to patients and in different communities. The aim of this study was to evaluate the clinical and epidemiological features, morbidity and mortality of pemphigus vulgaris and to compare that with other studies of different communities. Methods: It was an observational study, conducted on 24 hospital admitted cases of pemphigus vulgaris at the department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. The duration of the study was from November 2018 to February 2020. Patients who were confirmed as pemphigus vulgaris both histopathologically and direct immunofluroscent test were included for that study. Findings: The mean age (SD) of the patients was 47(15.5) years. Male outnumbered female in that study and male to female ratio was 1.4: 1. The mean (SD) duration of disease was 15(18.6) months. Pain (70.8) was the commonest symptoms. Trunk (92%) was the commonest cutaneous site of involvement followed by oral mucosa (71%). Oral prednisone was the mainstay of treatment and it was given to 24 (100%) of the patients. The immunosuppressant adjuvant was given in 79% cases. Azathioprine (62.5%) was the commonest of them. To avoid osteoporosis calcium supplement with or without vitamin D and bisphosphonate was given in 92% cases. The mean (SD) hospital stay was 5.4(3.3) weeks. Bacterial infection was the commonest complication and it was found in 2 patients. The mortality rate of that study was 4.16%. Conclusion: pemphigus vulgaris is a dermatological emergency and the maximum patients need hospitalization for proper care. Hospital acquired infections are the common complication and that may leads to septicemia and death. To decrease the mortality of pemphigus vulgaris the care givers have to be more watchful about the potential of infections. J Dhaka Med Coll. 2021; 29(1): 24-30